MINERALIZATION OF THE SELECTED BASE METAL DEPOSITS IN THE BARISAN RANGE, SUMATERA, INDONESIA (CASE STUDY AT LOKOP, DAIRI, LATONG, TANJUNG BALIT AND TUBOH) - Hamdan Z. Abidin; Harry Utoyo (Puslitbang tekMIRA, 2014)
Three types of base metal occurrences discovered along the Barisan Range, Sumatera are skarn, sedex and hydrothermal styles. The skarn styles include Lokop, Latong and Tuboh, while Dairi and Tanjung Balit belong to sedex and hydrothermal deposits, respectively. The Lokop deposit is dominated by galena with minor pyrite and is hosted within interbedded meta-sandstone, slate, phyllite, hornfels and quartzite of the Kluet Forma- tion. The Skarn Latong deposit consists of galena with minor sphalerite and chalcopyrite with skarn minerals of magnetite, garnet and calcite. It is hosted within the meta-limestone of the Kuantan Formation. The Skarn Tuboh deposit is dominated by sphalerite with minor galena, pyrite, manganese, hematite and magnetite. It is hosted within interbedded meta-sandstone and meta-limestone of the Rawas Formation. The Dairi deposit belongs to the sedimentary exhalative (sedex) type. It is hosted within the sedimentary sequence of the Kluet Formation. Two ore types known are Julu and Jehe mineralization. The Julu mineralization referring to as sediment exhalative (sedex), was formed syngenetically with carbonaceous shale. Ore mineralogies consist of galena, sphalerite and pyrite. The deposit was formed within the temperature range of 236-375°C with salinity ranges from 9,3-23% wt.NaCl. The Jehe mineralization which belongs to the Mississippi Valley-Type, is hosted within dolostone of the Jehe Member. Ores comprise galena, sphalerite, pyrite, chalcopyrite, tetrahedrite and tenantite. The deposit was formed at temperature range from 193-400°C with salinity up to 38.2% wt.NaCl. The Tanjung Balit deposit belongs to the hydrothermal mineralization. The deposit is hosted within the sedimentary sequence of the Silungkang Formation. Ores consist of chalcopyrite, galena and sphalerite with minor gold and silver. Hydrothermal minerals such as silica, illite, montmorillonite, pyropilite, muskovite, siderite, diaspor, dickite, magnesite, chlorite, carbonate, rhodochrosite, analcime, alunite, smectite, ankrite, calcite, dolomite, sericite and zeolite are common found. The Tanjung Balit mineralization is formed at the temperature range from 185-350°C and belongs to meso-epithermal type.